Effects of Characteristics and Perceptions of Collectors of Non-Timber Forest Products to be Members of the Partnership Program: A Case Study at Bukit Barisan Selatan National Park, Indonesia - Bakri, Samsul; Wulandari, Christine; Kurniasari, Nanda; Safe'i, Rahmat; Ramdani, Dadan; Anshory (Jurnal Manajemen Hutan Tropika, 2023)
Conservation partnerships are institutional innovations for self-empowering so that people are no longer dependent on forest areas. Initially, it regulated the relationship between the rights of non-timber forest product collectors (NTFPs) and their obligation to maintain sustainability, such as in the Bukit Barisan Selatan National Park (BBSNP). The high interest in becoming members has not been matched by the optimal implementation of the program that has been implemented since 2018 in the BBSNP traditional zone. Characteristics and perceptions are considered to have an influence on people's behavior in utilizing NTFPs and being interested in becoming members of the partnership. The aim of this research is to analyze the influence of community characteristics and perceptions on the utilization of NTFPs and their desire to become members of the partnership. Data collection used interviews and literature studies, analyzed statistically inferentially in December 2022 by testing the partial least square structural equation modeling (PLS-SEM) hypothesis using the Smart PLS.4.0 software for students with a sample of 62 respondents, namely the partnership permit applicant community. The results of the hypothesis test showed that the characteristics and utilization of NTFPs variables influenced the community's interest in becoming members of the conservation partnership. Perceptions affect the utilization of NTFPs variables. The use of NTFPs acts as a mediator between perceptions and interest in becoming a member. Misperceptions about conservation partnerships affect the implementation of the program. When public perceptions are improved through outreach activities, coaching etc will shape the character of the community to develop livelihoods and productive activities outside the area and stimulate voluntary leaving of the area without social conflict with area managers.